Praktik Sistem Nomokrasi Islam: Potret Kebebasan Ruang Publik Masyarakat Sipil Aceh - Junaidi, Junaidi; Rodiah, Ita (Prodi Tata Negara (Siyasah) IAIN Langsa, 2023)
The study examines the Islamic public sphere by exploring civil society access in Aceh. The Islamization of public space in Aceh can be attributed to the Islamic nomocracy system that has been implemented. Under this system, Islamic Sharia law serves as the fundamental framework governing all aspects of life in the Aceh region, as outlined in Law No. 18 of 2001, which granted Special Autonomy Status to Aceh and was later replaced by Law No. 11 of 2006 concerning the Aceh Government. The researcher's objective is to provide an overview of public space in Aceh, serving as a foundation for evaluating the effectiveness of Sharia implementation by the Indonesian government in Aceh. The research methodology employed in this study is library research, involving the examination of books, journal articles, notes, documents, previous research reports, and reports from internet websites. Content analysis techniques are utilized for data analysis. The study's findings reveal that the freedom of public space for civil society in Aceh is constrained by the Islamic nomocracy system in place. These constraints extend to various aspects, including politics, where not everyone enjoys the right to stand for election; finance, which mandates the use of Sharia-compliant financial systems; and religious discourse, which limits the expression of non-Muslims based on their beliefs. In addition, within Islam, religious discourse is confined to the Shafi'i, Asy'ari-Maturidi, and Imam al-Ghazali madhabs.